Aristotle’s objection against Forms in Metaphysics M.9 - González-Varela, Edgar (Revista Archai, 2020)
Aristotle formulates in Metaphysics M.9 an aporia about Forms, according to which, those who introduce Forms make them universal substances and, at the same time, separate entities and, hence, particulars. But, he claims, it is not possible that both attributes, being a universal and being a particular, inhere in the same thing. The interpretation that scholars have offered of this objection is external, in that they hold that it derives from Aristotle’s own conception of separation: only what is particular is separate. Here I defend an internal interpretation which claims that the objection derives from an assumption about the explanatory role of Forms that Aristotle attributes to the Platonists.